Identification and Characterization of Pig Embryo MicroRNAs by Solexa Sequencing. Issue 1 (31st May 2012) - Zhou, Y; Tang, X; Song, Q; Ji, Y; Wang, H; Wang, H; Jiao, H; Ouyang, H; Pang, D
Contents MicroRNAs (miRNAs) are a class of small, non‐coding RNAs of approximately 22 nucleotides in length that regulate gene expression by binding to the 3′‐untranslated regions of target mRNAs. It is now clear that miRNAs are involved in many biological processes, including proliferation, differentiation and regulation of gene expression during early embryonic development. The miRBase 16.0 (2010) shows that there are 175, 673, 408 and 1048 annotated miRNAs for Caenorhabditis elegans, Mus musculus, Rattus norvegicus and Homo sapiens, respectively. However, there are only 211 miRNAs described for Sus scrofa. In particular, the full set of miRNAs and their expression patterns are still poorly understood in the embryo. Therefore, we combined Solexa sequencing with computational techniques to analyse the sequences and relative expression levels of S. scrofa miRNAs at embryonic day 33 (E33). Of the distinct miRNAs identified, 76 previously known miRNAs and 194 candidate miRNAs were identified in head, and 77 known miRNAs and 130 predicted candidate miRNAs were identified in organ region. Furthermore, we performed additional investigation for identifying the potential target mRNAs using PicTar and TargetScan. Concurrent function analysis suggested that highly expressed miRNAs are mostly involved in the development of nerves, cerebrum, muscle and organs. Our results provide useful information for the investigation into embryonic miRNAs of pig and provide a valuable resource for investigators interested in the regulation of embryonic development in pigs and other animals.